Casualties of war - Fox, Michael J. 1961-; Penn, Sean 1960-; Rabe, David; Lang, Daniel; Morricone, Ennio (Clint Eastwood collection)
Based on the true story of a squad of soldiers caught in the moral quagmire of wartime Vietnam. Witness to a vile crime, Private Ericksson (Michael J. Fox) is forced to stand alone against his fellow soldiers and commanding officer Sergeant Meserve (Sean Penn). Master filmmaker Brian DePalma creates a devastating and unforgettable tale of one man's quest for sanity and justice amidst the chaos of war